Analisis Rasio Keuangan terhadap Return Saham Perusahaan Manufaktur di Bursa Efek Indonesia Sub Sektor Semen - Achmad Noor Affandi; Ardi Paminto; Muhammad Amin Kadafi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
Analysis of Financial Ratios Return Against Manufacturing Company Shares In BEI Cement Sub Sector. The purpose of this study to determine the Financial Ratio Of Stock Return of Manufacturing In BEI Sub Sector Cement, the basic theory diunakan management Financial Ratios Against Stock Return of Manufacturing In BEI Sub Sector Cement finance by using multiple linear regression analysis with the use of the sample 3 three companies in where each of brackish company 10 years. The conclusion of this study: Current Ratio partially have no significant effect on stock returns of companies manufacturing cement sub-sector in the Indonesia Stock Exchange. Thus the research hypothesis was rejected. Debt to Equity Ratio partially have a significant influence on stock return of manufacturing companies in the Indonesia Stock Exchange Sub cement sector. Thus the research hypothesis is accepted. Total Assets Turnover Ratio partially have no significant effect on stock returns of companies manufacturing cement sub-sector in the Indonesia Stock Exchange. Thus the research hypothesis was rejected. ROA partially have a significant influence on stock return of manufacturing companies in the Indonesia Stock Exchange Sub cement sector, so the hypothesis is rejected research is conducted PER partially have no significant effect on stock returns of companies manufacturing cement sub-sector in the Indonesia Stock Exchange, thus the research hypothesis is rejectedKeywords: Financial Ratios - Return Shares